Genome expansion and lineage-specific genetic innovations in the forest pathogenic fungi Armillaria. Issue 12 (December 2017) - Sipos, György; Prasanna, Arun; Walter, Mathias; O'Connor, Eoin; Bálint, Balázs; Krizsán, Krisztina; Kiss, Brigitta; Hess, Jaqueline; Varga, Torda; Slot, Jason; Riley, Robert; Bóka, Bettina; et al.
Abstract Armillaria species are both devastating forest pathogens and some of the largest terrestrial organisms on Earth. They forage for hosts and achieve immense colony sizes via rhizomorphs, root-like multicellular structures of clonal dispersal. Here, we sequenced and analysed the genomes of fourArmillaria species and performed RNA sequencing and quantitative proteomic analysis on the invasive and reproductive developmental stages ofA. ostoyae . Comparison with 22 related fungi revealed a significant genome expansion inArmillaria, affecting several pathogenicity-related genes, lignocellulose-degrading enzymes and lineage-specific genes expressed during rhizomorph development. Rhizomorphs express an evolutionarily young transcriptome that shares features with the transcriptomes of both fruiting bodies and vegetative mycelia. Several genes show concomitant upregulation in rhizomorphs and fruiting bodies and sharecis -regulatory signatures in their promoters, providing genetic and regulatory insights into complex multicellularity in fungi. Our results suggest that the evolution of the unique dispersal and pathogenicity mechanisms ofArmillaria might have drawn upon ancestral genetic toolkits for wood-decay, morphogenesis and complex multicellularity. Fungi of the genusArmillaria include devastating forest pathogens that cause root rot disease in many plants. Sequencing genomes and transcriptomes of several species, the authors reveal the genetic basis of dispersal, multicellular development and pathogenic mechanisms inArmillaria .